Epoxidized corn oil polyol-based composites polyurethane flexible foams, preparation, and characterization - Silva, Simone Adriane; Zawadzki, Sônia Faria; Barbosa, Ronilson Vasconcelos; Ramos, Luiz Pereira (Ciência e Natura, 2019)
Corn oil is a renewable resource useful for the preparation of polyols used in syntheses of polyurethane. The goal was to synthesize composites flexible foams from corn oil polyol obtained by epoxidation and 4,4’ – methylenebis (phenyl isocyanate) and evaluate their properties. It was used as filler inorganic clay (from up 2 to 5% of silica fume, montmorillonite, and bauxite). The samples were analyzed by DSC, TG, compressive properties and SEM analyses. On DSC analysis was observed the negative temperature of the glass transition for all the samples, and thermally stable up to 200°C. The composites flexible foams showed weakly resistance in the compressive strength and SEM test the specimens exhibited opened cells.